GE_GERICHTE C/28953/2010 vom 21. Oktober 2016 - GE Cour de justice (2016)
HONORAIRES ; ARCHITECTE ; CONTRAT D'ENTREPRISE ; LÉGITIMATION ACTIVE ET PASSIVE | CO.372.1; CO.364.1; CPC.317.1; CPC.317.2; CPC.316.3;